Women in economic and social transformation era: Issues and challenges - Hassan, Kalthum; Yusof, Rohana (Universiti Utara Malaysia Press, 2015)
This book was motivated by the desire of the authors to reveal various issues and livelihood strategies of women in developing countries managing current socio-economic challenges as the state of the world is changing rapidly.The changes have brought about problems and opportunities to women globally as women have become one of the key actors in promoting the changes.Women in the developing countries have gone through various phases of socio-economic changes that have changed their roles from family affairs managers to corporate/institutional managers and workers and small and large scale entrepreneurs.However, different from men, the roles as family affairs managers remain even though women have assumed various other roles in government and corporate world.